JAPANESE TYPOGRAPHY ESSENTIALS: JAPANESE TYPE BETWEEN JAPANESE & LATIN CHARACTER - Limantoro, Gray Hansen (Transpublika Publisher, 2024)
Japanese Graphic Design works have distinctive characteristics in the use of typography. The different writing systems of Japanese and Latin characters cause differences in the formation of typography. The research was conducted to explore the differences in character and arrangement between typography for phonetic symbols, ideography in script and Latin. The research was conducted by experiment through comparison, taking 5 font samples each from 3 different letter forms. The results of the research describe the differences in character formation, the basic axis of letters.